A Patient with Keratoconus, Axial Hyperopia and Pigmentary Retinopathy - Bajracharya, Leena; Lama, Ang Jangmu (Nepalese Journal of Ophthalmology, 2018)
Introduction: Keratoconus has been known to be associated with various ocular conditions.Objective: To describe a case of high hyperopia, keratoconus and pigmentary retinopathy.Case: An eight year old boy, whose initial refractive error was high hyperopia with short axial length of 20mm, presented as bilateral advanced keratoconus with acute hydrops in one eye. Subsequently his other eye also developed hydrops. He had nystagmus and pigmentary retinopathy from his infancy. He was managed conservatively and the hydrops resolved in both the eyes leaving paracentral scar in the cornea.Conclusion: The triad of keratoconus, high hyperopia and pigmentary retinopathy has been quite rare. There could be syndromic association between the three simultaneous ocular findings.